Antivirus effectiveness of ivermectin on dengue virus type 2 in Aedes albopictus - Xu, Tie-Long; Han, Yin; Liu, Wei; Pang, Xing-Ya; Zheng, Bin; Zhang, Yi; Zhou, Xiao-Nong (PLOS Neglected Tropical Diseases, 2018)
Author summary Dengue fever is one of neglected vector-borne tropical diseases with a 30-fold increase in global incidence recently. In 2012, World Health Organization set a goal to reduce dengue mortality by at least 50% by 2020. Being faced with more challenges in the dengue control programs, such as the increase of dengue outbreaks, lacking absolutely effective vaccine, rise of vector insecticide resistance and so on; innovative vector control tools are urgently needed for current control programs on dengue fever. To find a new avenue in vector control, we for the first time assessed the inhibiting effectiveness of ivermectin on dengue virus type 2 (DENV-2) inside Aedes mosquitoes. We found that about 80% Aedes albopictus mosquitoes were effectively infected with DENV-2 without treatment of ivermectin. But in the groups of ivermectin treatment, the infection rate of DENV-2 and the median of virus loads were significantly reduced by up to 49.63% and 99.99%, respectively. Both quantitatively and qualitatively inhibiting effects of ivermectin were detected. We found out that ivermectin was able to effectively inhibit the DENV-2 multiplication in Aedes albopictus, which may gave us a hint that using ivermectin in some control programs as a zooprophylaxis to block dengue epidemic through inhibiting DENV-2 in field Aedes mosquitoes.